Prevalence of Eating Disorders And Menstrual Ir- regularities Among Female Football Players - Molnar, Andor H.; Vidiczki-DÃ³czi, Andrea; Petrovszki, Zita; GyÅ‘ri, Ferenc (Arena-Journal of Physical Activities, 2017)
Purpose: In the present study the occurrence of eating disorders (EDs) and menstrual Â dysfunctions Â (MDs) Â was Â examined Â among Â physically Â inactive women (C) and elite female football players (FP). Methods: ED was investigated by EDI and SCOFF-test. MD was measured by questions on menstrual history. Â Results: Although there were a few participants in both groups who reached the Â cut-off Â scores Â in Â â€˜Drive Â for Thinnessâ€™ Â and Â â€˜Body Â Dissatisfactionâ€™ Â sub- scales of EDI, there were no significant differences between the rates. None of the participants passed the critical limit in the â€™Bulimiaâ€™ subscale. There was no significant difference between the average scores of the first three subscales of EDI in the two groups. The next five subscales of EDI mea- sure Â psychopathology Â commonly Â associated Â with, Â but Â not Â unique Â to, Â ED. We could observe significant difference only between the average score of â€˜Interpersonal Â Distrustâ€™ Â subscale. Â Depending Â on Â the Â SCOFF-test Â we Â could not observe any significant difference between the incidences of EDs in the groups. In the FP group the age of menarche was significantly older. Less FPs had oligomenorrhea, but there was no significant difference between the rates of secondary amenorrhea. The common incidence of EDs and MDs was the same in both groups.